BODIPY-Bridged Push-Pull Chromophores for Nonlinear Optical Applications - Ulrich, Gilles; Barsella, Alberto; Boeglin, Alex; Niu, Songlin; Ziessel, Raymond (Chemphyschem, 2014)
A set of linear and dissymmetric BODIPY‐bridged push–pull dyes are synthesized. The electron‐donating substituents are anisole and dialkylanilino groups. The strongly electron‐accepting moiety, a 1,1,4,4‐tetracyanobuta‐1,3‐diene (TCBD) group, is obtained by insertion of an electron‐rich ethyne into tetracyanoethylene. A nonlinear push–pull system is developed with a donor at the 5‐position of the BODIPY core and the acceptor at the 2‐position. All dyes are fully characterized and their electrochemical, linear and nonlinear optical properties are discussed. The linear optical properties of dialkylamino compounds show strong solvatochromic behavior and undergo drastic changes upon protonation. The strong push–pull systems are non‐fluorescent and the TCBD‐BODIPY dyes show diverse photochemistry and electrochemistry, with several reversible reduction waves for the tetracyanobutadiene moiety. The hyperpolarizability μβ of selected compounds is evaluated using the electric‐field‐induced second‐harmonic generation technique. Two of the TCBD‐BODIPY dyes show particularly high μβ (1.907 μm) values of 2050×10−48 and 5900×10−48 esu. In addition, one of these dyes shows a high NLO contrast upon protonation–deprotonation of the donor residue. Look into my dyes: BODIPY dyes functionalized with tetracyanobutadiene groups as electron acceptors (A) and anisole or dialkylaminophenyl fragments as electron donors (D) are investigated. These push–pull molecules are non‐fluorescent and are active in several reversible photochemical and electrochemical processes. The hyperpolarizability is particularly high for an unsymmetrical dye functionalized at orthogonal positions.